1974
DOI: 10.1136/hrt.36.3.265
|View full text |Cite
|
Sign up to set email alerts
|

Use of plasma levels in evaluation of procainamide dosage.

Abstract: Plasma procainamide levels achieved by oral procainamide treatment were studied in patients with recent myocardial infarction or ischaemia. Procainamide therapy was started after intravenous lignocaine had been used to control ventricular arrhythmias in the acute phase. A i g loading dose did not provoke toxicity and achieved 4-hour levels in or near the therapeutic range in 79 per cent ofpatients. Some patients with cardiac failure absorbed oral procainamide very slowly. A maintenance regimen of 375 mg 4 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1975
1975
1979
1979

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…There was a wide variation in individual peak values despite the relatively minor dose differences. This was previously reported by Koch-Weser &Klein (1971) andShaw et al (1974) using the conventional tablet and more recently by Cunningham, Sloman & Nyberg (1977) with Durules. Ihlen & Ditlefsen (1975) in a clinical trial comparing Durules and Retard reported a consistent difference in levels achieved 8 h after commencement of treatment, with Durules reaching higher levels than Retard.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…There was a wide variation in individual peak values despite the relatively minor dose differences. This was previously reported by Koch-Weser &Klein (1971) andShaw et al (1974) using the conventional tablet and more recently by Cunningham, Sloman & Nyberg (1977) with Durules. Ihlen & Ditlefsen (1975) in a clinical trial comparing Durules and Retard reported a consistent difference in levels achieved 8 h after commencement of treatment, with Durules reaching higher levels than Retard.…”
Section: Discussionsupporting
confidence: 52%
“…Its use as a prophylactic agent has been severely restricted by the short half-life of 3.5 h (Koch-Weser & Klein, 1971) of the conventional oral preparation (Pronestyl, procainamide hydrochloride, Squibb). This has meant that 3 hourly administration of the drug has been necessary to maintain therapeutic plasma levels (Koch-Weser et al, 1969;Shaw, Kumana, Royds, Padgham & Hamer, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…1972;Karlsson et al, 1974;Graffner, 1975). Furthermore, it is often 'abnormal' precisely in those clinical situations for which the drug is commonly used (Koch-Weser, 1971;Shaw et al. 1974).…”
Section: Unpredictable Dose-concentration Relationshipmentioning
confidence: 94%
“…1952;Enselberg and Lipkin, 1952;Bigger and Heissenbuttel, 1969;Gey et al. 1974;Shaw et al, 1974;Karlsson and Sonnhag, 1976;Karlsson et al, 1977).…”
Section: Establishment Of the Therapeutic Rangementioning
confidence: 98%
“…The frequency of adverse effects was higher in patients with both acute myocardial infarction and congestive failure than in those with either condition singly or with neither, although the results did not attain conventional levels of statistical significance. This is presumably due to the severity of the underlying cardiac disease, although it has also been reported that absorption of this drug is reduced and metabolism and excretion impaired in patients with cardiac failure (Shaw, Kumana, Royds, Padgham & Hamer, 1974;Biggar, 1975), and in the early phases after myocardial infarction (Koch-Weser, Klein, Foo-Canto, Kastor & de Sanctis, 1969). 45 Procainamide is excreted partly by the kidney and partly by hepatic transformation to N-acetylprocainamide.…”
Section: Methodsmentioning
confidence: 99%